2021
DOI: 10.3390/ijms222312805
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity and Underlying Mechanisms of Endogenous Neurotoxins

Abstract: Endogenous and exogenous neurotoxins are important factors leading to neurodegenerative diseases. In the 1980s, the discovery that 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) contributes to Parkinson’s disease (PD) symptoms led to new research investigations on neurotoxins. An abnormal metabolism of endogenous substances, such as condensation of bioamines with endogenous aldehydes, dopamine (DA) oxidation, and kynurenine pathway, can produce endogenous neurotoxins. Neurotoxins may damage the nervous sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 115 publications
0
21
0
Order By: Relevance
“…For example, MR studies rely on the assumption that the genetic variant does not affect the disease outcome except through exposure. However, the inactive ALDH2 genotype may increase the risk of depression by pathways other than alcohol exposure, such as pathways that involve endogenous aldehydes 21 . Moreover, inactive ALDH2 may act as an effect modifier that enhances alcohol toxicity in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…For example, MR studies rely on the assumption that the genetic variant does not affect the disease outcome except through exposure. However, the inactive ALDH2 genotype may increase the risk of depression by pathways other than alcohol exposure, such as pathways that involve endogenous aldehydes 21 . Moreover, inactive ALDH2 may act as an effect modifier that enhances alcohol toxicity in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Because IDO1 generates kynurenine from tryptophan, the cellular concentrations of tryptophan and kynurenine are decreased and increased by IDO1 expression, respectively. It has been reported that kynurenine induces several neurological and immunological alterations [ 45 , 46 ]. However, excess tryptophan overcame the antiviral activity of IDO1.…”
Section: Discussionmentioning
confidence: 99%
“…1 In certain circumstances, chemicals can also cause cell necrosis or apoptosis, leading to neuronal loss and causing neuropathy, and this neuronal loss is often irreversible and may lead to holistic encephalopathy. 2 If only subpopulations of neurons are affected, this may lead to the loss of specific functions of the nervous system. An example is the compound MPTP ( degeneration of nigrostriatal dopaminergic neurons, which in turn produces Parkinson's-like symptoms.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Generally, the neurotoxicity can be induced by several different patterns, including causing neuronal lesions, targeting axons and causing axonal lesions, inducing myelin lesions, and affecting neurotransmission . In certain circumstances, chemicals can also cause cell necrosis or apoptosis, leading to neuronal loss and causing neuropathy, and this neuronal loss is often irreversible and may lead to holistic encephalopathy . If only subpopulations of neurons are affected, this may lead to the loss of specific functions of the nervous system.…”
Section: Introductionmentioning
confidence: 99%